Desplazamiento Forzoso y Memoria. Narrativas de la Reconfiguración Familiar en Comunidad Afrodescendiente Asentada en Ciudad Bolívar – Bogotá (2018)
The present investigation was carried out with the objective of analyzing the family reconfiguration in the Afro-descendant community settled in Bolívar-Bogotá city, which for reasons associated with the search for better life opportunities or the armed conflict of the country, have reached the capital.